Experience in the Implementation of Programs for Primary Prevention of Human Papillomavirus-associated Diseases in the Moscow region - Zarochentseva, N. V.; Belaiya, J. M. (Èpidemiologiâ i vakcinoprofilaktika (Online), 2017)
The aim of the study was to evaluate the effectiveness of the programme of Human papillomavirus (HPV) vaccination and cervical cancer in girls and women in the Moscow region. Materials and methods. The statistical reports of the specialists of the Moscow region, as well as on the basis of data of state statistics to assessment of the incidence of anogenital warts in girls, as well as the dynamics of the incidence of cervical cancer in women in the Moscow region. Results. Based on the analysis of statistical reports of the Moscow region as a result of vaccination of girls observed a reduction in the incidence of anogenital warts in 2016 compared to 2009, from 14.2 to 5.9 (per 100 000 for girls). Based on date of the state ststistics there has been a reduction in the incidence of anogenital warts in the population in the Moscow region with up 56.7 to 20.2 (per 100-000 population). But the most important effect of vaccination in 2015 was the lack of a rise in the incidence of cervical cancer in women in the region, as well as the reduction in the incidence in young women aged 1524 years. Conclusion. Held in Moscow region the program of HPV vaccination and cervical cancer after 9 years resulted in a reduction of HPV-associated pathology, which determines the need to continue vaccination programs, including inclusion of vaccination in the immunization schedule.